Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Kota Kaediri (Berdasarkan Tahun 2000-2014) - Mauliana, Sella; , Drs. Triyono, M.Si (2017)
Economic growth is one of the long-term ecomonic problem and can be affected by several factors. This research was ucted to analyze what factors influenced in the local revenue. The place taken in this study in the city of Kediri and independent variables used are gross regional domestic product, population dan inflation in the year 2000-2014 and the local revenue as the dependent variable. This research carries the title of "Analysis of factor that affect the original income of the city of Kediri (based on the years 2000-2014). The method of analysis used is multiple linier regression model analysis method ordinary least square (OLS). This data used in this study using secondary data ( time series). Data obtained from the central statistical center of the city Kediri, Bank of Indonesia Kediri branch office and other relevant sources. Normal data stribution normality test result. Linierity test result in the form of linier. The results of the classic assumption test show that there is no problem mulitcollinearity, heterokedastisity but there are problem of autocorrelation. This in because there are squared variables. Model feasibility test results show that the dependent variable is influenced by independent variable aqual to 74,2%. F test show that simultaneously independent variable has significant effect to the dependent variable. The validity test of influence using t-test with the result of variable of gross domestic reginal product and the population have a significant effect to the original income , while inflation has not siginifikan effect. Keywords : economic of growth, locally-generated revenue, gross regional domestic product, population, inflation